Do Green Banking and ISR Create Firm Value? The Moderating of GCG in Islamic Banks - Aan Kanivia; Safitri Akbari; Nadzma Adelia Putrie; Nidzma Adelia Putrie (Politeknik Ganesha Medan, 2026)
Although sustainability disclosures are increasingly emphasized in Islamic finance, evidence on how environmental and sharia-based social disclosures are associated with firm value remains inconclusive, particularly in emerging markets. Prior studies mostly examine Green Banking Disclosure (GDB) and Islamic Social Reporting (ISR) separately and provide limited insight into the moderating role of corporate governance in Islamic banking. This study explores the relationship between GDB and ISR with firm value and examines the moderating role of Good Corporate Governance (GCG). Using a quantitative explanatory approach, secondary data from Islamic commercial banks listed on the Indonesia Stock Exchange during 2018–2024 are analyzed. Three banks were selected through purposive sampling, resulting in 21 firm-year observations. Data were obtained from annual reports, financial statements, and sustainability reports, and analyzed using multiple linear regression and moderated regression analysis. The results indicate that GDB is negatively associated with firm value, suggesting that environmental disclosure is perceived by the market as a short-term cost. Institutional ownership and independent boards condition and intensify the negative association between GDB and firm value, while audit committees show no moderating role. No governance mechanism moderates the relationship between ISR and firm value. This study contributes by integrating environmental and Islamic social disclosures within a unified framework and highlighting the context-dependent and selective role of corporate governance in shaping sustainability-related value perceptions in Islamic banking.